Diagenesis and elemental geochemistry under varying reservoir oil saturation in the Junggar Basin of NW China: implication for differentiating hydrocarbon‐bearing horizons. Issue 3 (1st October 2014) - Cao, J.; Hu, W.; Wang, X.; Zhu, D.; Tang, Y.; Xiang, B.; Wu, M.
Abstract In this paper, we attempt to differentiate hydrocarbon‐bearing reservoir horizons of the Junggar Basin of NW China based on the characteristics of diagenesis and associated elemental geochemistry. Reservoirs at this site have varying levels of oil saturation that correlate with the degree of dissolution in minerals (e.g., calcite and feldspar). Four different horizons with varying diagenetic mineral assemblages were observed, including (i) kaolinite‐rich, oil‐dominated horizons, (ii) kaolinite–pyrite–hematite‐rich, oil–water‐dominated horizons, (iii) siderite–chlorite‐rich, water‐dominated horizons, and (iv) chlorite‐rich horizons with negligible hydrocarbon production. The mean MnO content of the representative diagenetic mineral (e.g., calcite) in each of the above horizons is >2.5, 2.0–2.5, 1.5–2.0, and <1.0 wt%, respectively. We propose that the above methodology can be used for the identification of reservoir hydrocarbon‐bearing horizons. We argue that the indicators presented here can be applied in oil exploration across the Junggar Basin.